Kurdish Revolution of Aylul (September) in British Financial Times 1963- 1975 - Mohammed, Sherzad Z. (Humanities Journal of University of Zakho, 2016)
The British press has given a clear interest about the developments of the political situation in Kurdistan -Iraq after the outbreak of September 1961 revolution, and among the most prominent newspapers was the Financial Times. Despite the fact that the newspaper’s concerns are mainly focused on the economic aspects; nevertheless it has allocated several reports and articles for Kurdistan and its revolutions. The sources from which the newspaper got reports from varied, but mostly the correspondents of the newspaper in Beirut, Ankara, Tehran and in the Middle East were sending reports. Additionally, in one occasion, one of its correspondents actually visited Kurdistan and Iraq, and sent his reports from the ground. It is worth noting that the paper did not address the Kurdish revolution until 1963, after the resumption of fighting in Kurdistan then it began writing about the Kurds with limited coverage and not up to the level of events until 1974. In that year, the newspaper’s reporters covered the news of the revolution more broadly and closely. To an extent, the reports published in this period were marked by abundance and richness of information. Thus, this newspaper can be considered as an indispensable source for September’s revolution in Kurdistan.